Aagaard & Bouteneff's "Beyond the East-West Divide: The World Council of Churches and the Orthodox Problem" - Book Review - Gavriljuk, Pavel L. (Religion in Eastern Europe, 2004)
Anna Marie Aagaard and Peter Bouteneff, Beyond t e East-West Divide: The World Council of Churches and “the rthodox Problem.” Geneva: W CC Publications, 2001.